Factors Associated with Tooth Loss in Older Adults in Rural Colorado - Tiwari, Tamanna (J Community Health, 2016)
The purpose of this paper is to examine factors that are associated with tooth loss in older adults living in the San Luis Valley (SLV), Colorado, which is a rural and large geographical area (roughly the size of Connecticut) that has a large population age 60 years or older. Data used in this manuscript were collected as a part of the SLV Community Health Survey. The analyzed sample included 308 adults over the age of 65 years who completed the survey. Basic descriptive statistics and a series of step-wise binary logistic regression analyses were conducted; the dependent variable was the number of permanent teeth removed because of tooth decay or gum disease. Fifty-two percent of the participants were male, Hispanic participants made up 40 % of the sample and 76 % of the participants had at least a high school education. Tooth loss was significantly associated with older age (OR = 1.09; p = 0.02), lower income (OR = 0.01; p = 0.00), less than high school education (OR = 0.32; p = 0.01), being Hispanic (OR = 2.15; p = 0.05), self-reported fair-poor health status (OR 2.94; p = 0.02), consumption of one or more than one sweet beverage per day (OR = 4.52; p = 0.00), no dental insurance (OR = 4.70; p = 0.01) and length of time since last dental visit (OR = 0.21; p = 0.01). The findings of the present study suggest possible causes for tooth loss in rural adults and underscore the need for in-depth research to study the overall oral health of rural older adults living in SLV.